Crow planet : essential wisdom from the urban wilderness - Haupt, Lyanda Lynn (Back Bay Books, 2011)
A scholarly tribute to crow life and mythology explains how increasing crow populations are reflecting various ecological imbalances while providing opportunities to connect with the animal world.